Cost of production of bovine milk in three silvopastoral systems: alder (Alnus acuminata), acacia (Acacia melanoxylon) and a control with forage mix - Carvajal Pérez, Luis Alfredo; Benavides Rosales, Hernán Rigoberto; Caicedo Rosero, Diego Marcelo (Tierra Infinita, 2019)
The dairy sector is one of the most important in the economy of the province of Carchi, it is annual production is among the highest in the northern highlands. However, this sector has a common weakness and is an empirical management of its production costs. This failure causes inaccuracies when evaluating the real profitability of its production system and disables many possibilities for improving the economic efficiency of it. This study was carried out in order to determine the types of inputs with the highest incidence in the production cost of the liter of milk, establish the cost of production per liter of milk of the agro ecosystem and analyze the productive efficiency between systems.